The Influence of Crossword Puzzle Science Learning Media toward Students’ Critical Thinking Ability - Mardhatillah, Syafna; Anas, Nirwana (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study aims to determine whether the Crossword Puzzle media has an effect on Critical Thinking of Class III students of MIS Farhan Syarif Hidayah on Jalan Orde Baru Gg, pipit Desa Muliorejo Kec. Sunggal district. Serdang deli. This research is a quantitative study using quasi-experimental methods. The research design used was a non-equivalent control group design. The population for this study was class III A consist of twenty students as experiment Â and class III B MIS consist of twenty students as control class. Â The results showed that there were differences in the ability to think critically on the subject of the characteristics of living things. The increase in critical thinking skills can be seen in the results of students’ critical thinking tests in the experimental class after using crossword puzzle learning media and before using crossword puzzle learning media. The average post-test score for the experimental class was 84.50 and the post-test average score for the control class was 72.50. It can be concluded that there is an influence of the Crossword Puzzle learning method on students’ critical thinking skills in class III MIS Farhan Syarif Hidayah and according to Researchers using crossword puzzle learning media can help students in repetition and habituation activities, so that students will easily learn material that is difficult in natural sciences. Learning media functions as a learning resource and a way for students to obtain information from the teacher. The benefits of learning media include guidelines for teachers to achieve quality learning objectives, increase students’ interest and motivation in learning and make students think more critically.